Pengembangan Media Pembelajaran Video Animasi pada Topologi Jaringan untuk Siswa Kelas X Teknik Komputer dan Jaringan - Seto, Bayu Seto Pamungkas; Ismail; Hamda Kharisma Putra; Fauziah, Syifa (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to study the process of developing animated video media on network topology material for class X vocational schools, measure students' interest and learning outcomes after using animated video learning media on network topology subjects and determine the validity of Computer Engineering and Network (NE) learning media at Jumantono State Vocational School. The research method uses the ADDIE model. The research procedure includes the production of learning media using the Sony Vegas Pro application, then validated by media experts, material experts and student respondents. Effectiveness testing is carried out by measuring student test results before and after using learning media. Data analysis using T-test on SPSS version 26 application. The results of the study showed that the results of the development of animated video media with the content of network topology subjects obtained a value from media experts of 3.5, material experts of 3.3 and student responses with an average of 3.5 with good criteria. The effectiveness of the media showed that the results of the pre-test of students who liked the subject of network topology or not increased from 67.5 to 85 and 63.5 to 77. The conclusion of the study is that animated video media is feasible and ready to be used to improve the interest and learning outcomes of class X students of computer engineering and networks at Jumantono vocational high school.